2015
DOI: 10.5539/gjhs.v7n6p338
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Anger among Male Adolescents in Western Iran: An Application of Social Cognitive Theory

Abstract: Introduction:Anger can be defined a natural emotional response that is gradually formed to protect us in dealing with threats, damages, assaults, and failures; while hatred is a change of attitude which is built following the persistence of anger towards a subject or an individual. One of the main reasons of adolescents’ reference to the counseling centers is their anger accompanied by violence.Objective:This study aims to determine the social cognitive factors associated with anger among a population of adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…On the other hand, in the earlier studies conducted with the target population of patients, 32,35,37,38 typically, subjective norms have shown a more significant role in predicting intention. Usually, human behavior gets influence by nearby people such as medical staff, than healthy people.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, in the earlier studies conducted with the target population of patients, 32,35,37,38 typically, subjective norms have shown a more significant role in predicting intention. Usually, human behavior gets influence by nearby people such as medical staff, than healthy people.…”
Section: Discussionmentioning
confidence: 80%
“…Conversely, some studies showed a significant relationship between students' knowledge and the rate of aggression. 56,57 Given the comparison of teachers’ knowledge scores of parents and students and their level of education toward two groups, teachers lacked a high level of knowledge toward the types of aggression. Similar to our study, various studies suggested that most teachers lacked a clear understanding of the definition of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated a positive and significant relationship between outcome expectancies and aggression, that was consistent with the results of our study. 56,63…”
Section: Discussionmentioning
confidence: 99%
“…Each item ranked by participants along five-point continuum scale, ranged from "extremely characteristic of me (5)…”
Section: Scoring Systemmentioning
confidence: 99%
“…In this period of life, aggression may probably predict delinquency, drug abuse, depressive symptoms, and academic disappointment. In fact, the anger associated with aggression is among the main motives for referral of adolescents to counseling centers (5) .…”
Section: Introductionmentioning
confidence: 99%